Pengaruh Store Atmosphere Dan Promosi Terhadap Impulse Buying Dengan Positif Emotion Sebagai Variabel Intervening - Nainggolan, Benhart (Digital Business Progress, 2025)
This study aims to analyze "The Influence of Store Atmosphere and Promotion on Impulse Buying with Positive Emotion as an Intervening Variable (Case Study at Alfamart Yos Sudarso, Tebing Tinggi City). Based on the results of the analysis of hypothesis 1, the Store Atmosphere variable (X1) has an effect on Positive Emotion (Z). Based on the results of the analysis of hypothesis 2, the Promotion variable (X2) has an effect on Positive Emotion (Z). Based on the results of the analysis of hypothesis 3, the Store Atmosphere variable (X1) does not have an effect on Impulse Buying (Y). Based on the results of the analysis of hypothesis 4, the Promotion variable (X2) has an effect on Impulse Buying (Y). Based on the results of the analysis of hypothesis 5, the Positive Emotion variable (Z) does not have an effect on Impulse Buying (Y). Based on the results of the analysis of hypothesis 6, the Positive Emotion (Z) variable can mediate the relationship between Store Atmosphere (X1) and Impulse Buying (Y). Based on the results of the analysis of hypothesis 7, the Positive Emotion (Z) variable cannot mediate the relationship between Promotion (X1) and Impulse Buying (Y).